Rätten till integritet vid bekämpning av penningtvätt - En undersökning av motstridiga krav mellan AML-regleringen och dataskyddsförordningen - Andersson,Sara (2026)
The fight against money laundering constitutes a central public interest within the European Union and has resulted in an extensive regulatory framework imposing far-reaching obligations on obliged entities to process and retain personal data. At the same time, the protection of personal privacy has been strengthened through the EU General Data Protection Regulation (GDPR). Although these regulatory frameworks are not inherently contradictory, their parallel application to the same personal data processing requires an ongoing legal balancing. The issue is particularly evident in digital financial services, where credit institutions, payment institutions, and other actors carry out large-scale automated customer due diligence and monitoring measures. The purpose of this thesis is to analyse how the requirements for personal data processing under the anti-money laundering (AML) framework should be applied in relation to the privacy protections established by the GDPR. The analysis focuses on the retention of customer due diligence data and limitations to the duty to provide information when reporting suspicious transactions. The study is based on EU law and Swedish law and evaluates these measures in light of the EU Charter of Funda-mental Rights. A legal dogmatic method is applied. The findings show that the AML framework, in principle, entails legitimate restrictions on personal privacy justified by a significant public interest. However, the analysis also demonstrates that general retention periods and broad confidentiality exceptions risk exceeding what is necessary in individual cases, particularly with regard to low-risk customers. This highlights the need for a more nuanced application in which effective crime prevention is balanced with meaningful data protection.
Keywords: penningtvätt; AML; GDPR; dataskydd; öppenhetsprincipen; fintech; kundkännedom; informationsskyldighet; Anti-Money Laundering; data protection; the principle of proportionality; Customer Due Diligence.